Covalent and non-covalent strategies for surface modification of different textile materials with antimicrobial properties - Nogueira, Frederico Álvaro Sequeira (2018)
Nowadays, millions of people become infected with bacteria that cause hospital infections, which is a major cause of mortality in hospitals, killing 700,000 people per year in the world. It is even projected that the number of deaths in hospitals will grow to 10 million by 2050. The use of antimicrobial textiles, especially in close contact with the patients and in the immediate and non-immediate surroundings, may significantly reduce the risk of infections. However, they should possess broad spectrum biocidal properties, be safe for use and highly effective against antibiotic resistant microorganisms, including those that are commonly involved in hospital-acquired infections. Most nosocomial infections are primarily by opportunistic microorganisms, i. e., they rarely cause diseases in a healthy immune system, but seek to exploit any weaknesses in the body of immunocompromised patients, such as victims of burns, cancer patients or beddriden with open wounds, in order to cause infections. These strains have the ability to grow in any environment, present important virulence factors, and have resistance to a large variety of antibiotics. Several antimicrobial agents have been tested in textiles. Quaternary ammonium compounds, silver, polyhexamethylene biguanides and triclosan have been used, with limited success. They have powerful bactericidal activity, however, the majority have a reduced spectrum of microbial inhibition and may cause skin irritation, citotoxicity, ecotoxicity and bacterial resistance. In addition, its incorporation in the textiles reduces their activity substantially and limits availability. Moreover, the biocide can gradually lose activity during the use and textile repeated laundering. To overcome these disadvantages, natural compounds such as L-Cysteine (L-Cys), bacteriophages and antimicrobial peptides (AMPs), were tested in this work as antimicrobial agents for fibrous materials. As such, in a first approach we carried out studies in order to confer antimicrobial properties on textile and polymeric surfaces in such a way that they could irreversibly attract, bind and eliminate microorganisms, paving the way to a dynamic protective barrier. For this purpose, the amino acid L-Cys and the AMPs Magainin I, LL-37, and Cys-LC-LL-37 were used in order to provide antimicrobial properties to cotton fibrous materials . L-Cys was selected due to its proven antimicrobial properties granted by its thiol group and also proved its capacity to ensure antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) reagent. Covalent and non-covalent immobilization strategies were tested on different fibrous materials and subjected to intensive washing cycles, such as cotton, silk, polycaprolactone, and polypropylene, in order to immobilize L-Cys in a durable manner. For a better understanding of the interactions material-L-Cys-bacteria, cotton textile substrates were chemically modified with N, N-carbonyldiimidazole (CDI) and subsequently functionalized with different concentrations of L-Cys. These studies revealed that there was a specific amount of CDI activator (4%) which would be ideal to more efficiently bind L-Cys (5%). These results revealed a higher antimicrobial efficiency, when compared to another study, in which the cotton substrate was non-covalently immobilized with Magainin I and LL-37. Cotton-L-Cys caused most death among bacteria, after washing cycles, due exclusively to its covalent bound that was able to immobilize L-Cys more permanently. In support of this hypothesis, a polymer difficult to modify - polypropylene - was grafted with L-Cys, which strengthened its nanostructure and endowed it with thiol groups that allowed to bind the peptide Cys-LC-LL-37 via disulfide bond (covalent). It was found that Cys-LC-LL-37 resisted to successive wash cycles, and the flexibility of this peptide was unique to the elimination of the microorganisms. Subsequently, the knowledge acquired when using cotton and polypropylene were transferred to silk and polycaprolactone, in order to test the applicability of this developed concept to other fibrous structures potentially to be used as antimicrobial textiles. Different percentages of L-Cys were immobilized, by different chemical reactions, on samples of aforementioned polymers with biomedical potential, and X-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FT-IR), calorimetry (DSC), Ellman's reagent, and contact angle were used to chemically check L-Cys immobilization, as well as antimicrobial and cytotoxicity assays, so as to ensure that the applications would not be toxic to humans. Also, silk and polycaprolactone samples covalently bound by 1 and 5% L-Cys, respectively, eliminated very well the microorganisms. In addition, these samples retained L-Cys during several wash cycles. At this stage, after the work developed and the knowledge acquired, enabled us to move into a new strategy of immobilization of bacteriophages in fibrous materials. The covalent coupling of the vB-Pae-Kakheti phage capsid to the surface of polycaprolactone nanofibers produced by electrospinning was performed, so that the phage had its tail facing outwards, maintaining its infectivity. The results again confirm that not only the presence of an antimicrobial, but also the way it is immobilized, makes all the difference in the development strategy of antimicrobial textiles. It was concluded, therefore, that an optimized amount of "new" antimicrobial compounds alternative to antibiotics and synthetic biocides, as well as their specific orientation, consisted of a better performance upon contact and elimination of bacteria, being crucial for the development of biomaterials for contact with skin and mucosa.